12 Novel analysis of hospital episode statistics underpins collaborative project supporting the optimisation of local pathways for non-ST elevation acute coronary syndromes (NSTE-ACS) – HES copyright 2017; re-used with the permission of NHS digital. (June 2018) - Jones, Richard; Beckett, Matthew; Brander, Simon; McConnon, Henrietta; Fairbrother, Karen
Abstract : Background: Local NSTE-ACS pathways and time to treatment vary widely across the UK. Supported by the NICE Implementation Collaborative, the Cardiovascular Partnership Programme is a Medical Education, Goods and Services initiative from AstraZeneca that provides clinical leadership and support to hospital Trusts looking to reform pathways and ensure patients receiving procedures (angiography or PCI) do so within NICE recommended guidelines of 72 hours. Key to this is meaningful data that follows the whole pathway from initial admission through to procedure inclusive of transfers across Trusts. Methods: A novel analysis of HES admissions (spells) was used to generate a database of pathways. Initial spells were linked to follow-on procedural spells to create super spells for the 2016–17 period. Relevant spells were identified using a sequential approach to search for ICD-10 codes within an admission. Based on the National Clinical Coding Standards ICD-10 5th Edition (2016), anchor spells were identified with a primary diagnosis of STEMI (I21.0–3) or NSTEMI (I21.4). Also included were MI unspecified (I21.9, I21.X) and UA (unstable angina I20.0). Follow-on spells were identified by OPCS codes for angiography (K63, K65), PCI (K49–50, K75) or CABG (K40–46), an admission start date within 28 days of an anchor start date and either a primary diagnosis of atherosclerotic heart disease (I25.1) with non-primary anchor diagnosis or a primary diagnosis of subsequent MI (I22). Anchor spells with a procedure, coded as transfers and with an immediately preceding spell were reassigned as follow-ups. CSL's analytical tool Esprit was used to interrogate the database. This project focused on hospital pathways and days from first admission to procedure for NSTEMI and UA. Results: There were 65 330 initial NSTE-ACS admissions, 5% of these being readmissions within 3 months of a previous ACS admission. CABG was coded in 5% of super spells, whilst 31% had a code for PCI (no CABG) and 21% angiography alone. Of 36 654 with a date of procedure, 44% of these (45% for NSTEMI alone) were within 3 days of initial admission and the average days to procedure was 4.0 (range 1.6–8.7 days). 19% of Trusts providing procedures (28% for NSTEMI) achieved >60% of those in <3 days. Of admissions with a record of procedure, 70% were direct admissions (or initial hospital admission not identified), 6% were direct transfers within Trust, 21% were direct transfers from outside the Trust, 3% had insufficient site information or an indirect transfer. Conclusion: This novel database has provided new insight into ACS pathways. It looks at days from very first admission to catheter lab and excludes preliminary angiography prior to PCI. Trusts are able to reliably compare the efficiency of their NSTE-ACS pathway to drive quality improvement and help them work to Best Practice Tariff targets of >60% NSTEMI admissions receiving angiography within 72 hours.